Air-thermal processing of hierarchically porous metal–organic frameworks. Issue 26 (30th June 2020) - Jia, Miaomiao; Mai, Lei; Li, Zhanjun; Li, Wanbin
Abstract : An air-thermal processing strategy is developed to remove residual solvents and uncoordinated linkers for redesigning metal–organic frameworks with improved adsorption proprieties and hierarchically micro/meso/macroporous superstructures. Abstract : Metal–organic frameworks (MOFs) show great potential for various applications. The functions of MOFs are closely related to their porous structures and lattice integrities. However, the generally existing guest solvent/linker molecules and crystalline defects will alter internal microstructures and microenvironments of MOFs. Meanwhile, although MOFs have tailorable pore structures within the range of microspores, the achievement of meso/macropores in MOFs is of scientific interest. Herein, a versatile air-thermal processing (ATP) strategy is reported to remove the residual molecules and incompletely coordinated linkers in MOFs. Through processing MOFs in confined space, the thermalized and pressurized air can assist the filling solvents and partially/totally uncoordinated linkers to overcome the energy barrier of escape, and then maximize MOF porosity. The obtained MOF materials with hierarchical micro/mesoporous structures display substantially improved adsorption capacities and selectivities. For example, CuBTC-A shows 36%, 72%, 22%, and 86% enhancements in surface area, pore volume, CO2 uptake, and CO2 /N2 selectivity, respectively. Moreover, by adjusting processing temperature, the ATP strategy is available for fabricating MOF materials with hierarchically micro/meso/macroporous superstructures under modulator/template-free conditions.